2020
DOI: 10.1037/pspa0000184
|View full text |Cite
|
Sign up to set email alerts
|

Salience theory of mere exposure: Relative exposure increases liking, extremity, and emotional intensity.

Abstract: We propose and support a salience explanation of exposure effects. We suggest that repeated exposure to stimuli influences evaluations by increasing salience, the relative quality of standing out from other competing stimuli. In Experiments 1 and 2, we manipulated exposure, presenting some stimuli 9 times and other stimuli 3 times, 1 time, or 0 times, as in previous mere exposure research. Exposure increased liking, replicating previous research (Zajonc, 1968), and increased salience, made evaluations more ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 125 publications
4
33
4
2
Order By: Relevance
“…A possible explanation for this finding is that participants habituate to the redundantly paired US pictures, which then perpetually lose their affective potential. Though we cannot rule out affective fading as contributing factor entirely, Experiments 3 and 4 found that participants evaluated the redundantly paired pictures as more and not less evaluatively extreme than the distinctly paired pictures, which is in line with recent research showing that repetition increases subjective affective extremity of stimuli (Mrkva & van Boven, 2020). The distinctly paired US pictures thus had a stronger influence on the brand evaluations than the redundantly paired pictures although they were perceived as less evaluatively extreme.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A possible explanation for this finding is that participants habituate to the redundantly paired US pictures, which then perpetually lose their affective potential. Though we cannot rule out affective fading as contributing factor entirely, Experiments 3 and 4 found that participants evaluated the redundantly paired pictures as more and not less evaluatively extreme than the distinctly paired pictures, which is in line with recent research showing that repetition increases subjective affective extremity of stimuli (Mrkva & van Boven, 2020). The distinctly paired US pictures thus had a stronger influence on the brand evaluations than the redundantly paired pictures although they were perceived as less evaluatively extreme.…”
Section: Discussionsupporting
confidence: 88%
“…For example, when a participant is exposed to a negative picture for the first time, the picture may elicit strong negative affect which is then transferred to the CS brand, whereas this affective potential may decrease when the same US picture is encountered repeatedly. Although recent research has found that repeated exposure to stimuli increases and not decreases subjective affective intensity of stimuli (Mrkva & Van Boven, 2020), it is nevertheless important to test a possible habituation explanation. Experiment 3 therefore aimed to replicate Experiment 2 and also asked participants to evaluate the US pictures at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Also emphasizing individual learning, Forster, Gerger, & Leder (2015) showed that an effect of ease of processing could only be found in within-participant (not between-subject) comparisons. Similarly, relative exposure, i.e., being presented more often than other stimuli in the set, increases liking more than absolute exposure (Mrkva & Van Boven, 2020). Together, such findings suggest that participants implicitly track the expected fluency across the recent history of experiences and attribute value to deviations from this expectation, a notion that will become important later on.…”
Section: Appreciationmentioning
confidence: 80%
“…It is crucial to inspect the underlying mechanisms biased by gaze manipulation that directly influence animacy perception. Attentional bias results in changes in the target's characteristics such as saliency, liking [61], and familiarity [54].…”
Section: Future Directionsmentioning
confidence: 99%